تنفيذ إدارة وقف النقدي )دراسة حالة في وحدة المعاونة والجمع ألموال الزكاة واإلنفاق والصدقة والوقف بيت المال هداية اهلل بماديون عام -2019 2020 م( - Aqif Khilmia Khilmia (Faculty of Economics and Management, 2020)
Waqf is one of the financial instruments that have an important position inIslamic civilization. Aside from being a source of funding for social, educational,and health activities, waqf can be used as alternatives for strengthening thecommunity's economy. The potential of cash waqf in Indonesia every month isaround 5.725 trillion rupiahs, assuming that all 229 million Indonesian Muslimsdonate 25 thousand rupiahs. To achieve optimal cash waqf management, it isnecessary to have management in the cash waqf management agency so that thepotential for cash waqf can be used optimally for the benefit of people. The purposeof this study is to determine the implementation of cash waqf management, inparticular, the collection and distribution of cash waqf funds in the AssistanceUnit for Baitul Maal Hidayatullah (UPP BMH) Madiun. This type of researchis exploratory qualitative research. Data collection is done through observation,interviews, and study documentation. As for analysis, this study uses inductiveanalysis, deductive analysis, and content analysis to describe the research object.The results of the study explain that the implementation of cash waqf managementin UPP BMH Madiun is managed by applying four management concepts whichinclude Planning, Organizing, Actuating, and Controlling in collecting fundscash waqf. In the collection of waqf funds, Planning is in the form of periodicplanning, namely annual, monthly, weekly, and housing and certain times. Asfor the aspect, it is Organizing carried out through the division of the Institutionstructure consisting of the chairman, HR and finance division, and fundraising.While actuating, it is carried out thoroughly in all divisions. The last aspect isControlling which is directly under the supervision of the head of the institutionassisted by the human resources and finance department. As for the distributionusing the POAC method and adapted to what is needed by Madiun community,such as land acquisition, educational scholarship for a student of Tahfidz, construction of ablution places in various mosques as well as providing Al-Qur'anmanuscripts.